An impaired metabolism of nucleotides underpins a novel mechanism of cardiac remodeling leading to Huntington's disease related cardiomyopathy - Toczek,M; Zielonka,D; Zukowska,P; Marcinkowski,JT; Slominska,E; Isalan,M; Smolenski,RT; Mielcarek,M (BBA - Molecular Basis of Disease, 2016)
Huntington's disease (HD) is mainly thought of as a neurological disease, but multiple epidemiological studies havedemonstrated a number of cardiovascular events leading to heart failure in HD patients. Our recent studies showed anincreased risk of heart contractile dysfunction and dilated cardiomyopathy in HD pre-clinical models. This could potentiallyinvolve metabolic remodeling, that is a typical feature of the failing heart, with reduced activities of high energyphosphate generating pathways. In this study, we sought to identify metabolic abnormalities leading to HD-related cardiomyopathyin pre-clinical and clinical settings. We found that HD mouse models developed a profound deteriorationin cardiac energy equilibrium, despite AMP-activated protein kinase hyperphosphorylation. This was accompanied by areduced glucose usage and a significant deregulation of genes involved in de novo purine biosynthesis, in conversion ofadenine nucleotides, and in adenosine metabolism. Consequently, we observed increased levels of nucleotide catabolitessuch as inosine, hypoxanthine, xanthine and uric acid, in murine and human HD serum. These effects may be causedlocally by mutant HTT, via gain or loss of function effects, or distally by a lack of trophic signals from central nerve stimulation.Either may lead to energy equilibrium imbalances in cardiac cells, with activation of nucleotide catabolism plusan inhibition of re-synthesis. Our study suggests that future therapies should target cardiac mitochondrial dysfunction toameliorate energetic dysfunction. Importantly, we describe the first set of biomarkers related to heart and skeletal muscledysfunction in both pre-clinical and clinical HD settings.